2019
DOI: 10.1002/pbc.27803
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcomes in classic Hodgkin lymphoma post‐transplant lymphoproliferative disorder in children

Abstract: Classic Hodgkin lymphoma post‐transplant lymphoproliferative disorder (HL‐PTLD) has been rarely reported in children, with limited data available to guide treatment decisions. We report a retrospective review of five children diagnosed with classic HL‐PTLD following solid organ transplant between 2007 and 2013 at Stanford University. Patients were treated with Stanford V chemotherapy and involved field radiation therapy. With a median follow‐up of 7.2 years (range, 4.7–10.5 years) since diagnosis, all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, a recent comparative study analysis between HL-PTLD after SOT and general HL adult patients suggested HL-specific chemotherapy regimens improved overall survival and chemotherapy-related toxicities were not significantly different among the 2 groups 4. Another study did report higher incidence of febrile neutropenia and infectious complications in HL-PTLD after SOT pediatric patients 11. Thus, because of therapy-related toxicities, chemotherapy dose modification was common in patients with CHL-PTLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent comparative study analysis between HL-PTLD after SOT and general HL adult patients suggested HL-specific chemotherapy regimens improved overall survival and chemotherapy-related toxicities were not significantly different among the 2 groups 4. Another study did report higher incidence of febrile neutropenia and infectious complications in HL-PTLD after SOT pediatric patients 11. Thus, because of therapy-related toxicities, chemotherapy dose modification was common in patients with CHL-PTLD.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another study did report higher incidence of febrile neutropenia and infectious complications in HL-PTLD after SOT pediatric patients. 11 Thus, because of therapy-related toxicities, chemotherapy dose modification was common in patients with CHL-PTLD. Some therapyrelated toxicities reported were grade III-IV neutropenia, myelosuppression and sepsis with 2-to 5-year event free survival shown to be 80% 12 (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…T-cell lymphomas do not respond to rituximab and should be treated according to their pathology. Patients with classic Hodgkin lymphoma-like PTLD (the least frequent type of PTLD) should be treated according to the treatment standards of Hodgkin-lymphomas (112)(113)(114).…”
Section: Treatmentmentioning
confidence: 99%